Implementation of The Regent of Cirebon Regulation Number 66 of 2021 on Talent Management of Civil Servants within The Cirebon Regency Government - Setiadi, Ade; Erna, Erna; Muttaqien, Prio Ilham (Universitas Negeri Semarang, 2025)
This research analyzes the implementation of the Regent of Cirebon Regulation Number 66 of 2021 concerning the Talent Management System for Civil Servants (Aparatur Sipil Negara, ASN) within the Cirebon Regency Government. The policy aims to create a professional, accountable, and competitive bureaucracy through the systematic development of human resources based on merit principles. However, in practice, several challenges emerge, including inadequate understanding of talent management concepts, uneven competence mapping, and limited digital integration in the implementation process. This study applies a qualitative descriptive approach, focusing on the analysis of policy implementation according to the model proposed by Edward III (1980), which emphasizes four key variables: communication, resources, disposition, and bureaucratic structure. Data were collected through interviews with officials from the Regional Civil Service and Human Resource Development Agency (BKPSDM), document analysis, and field observation. The research also employed secondary data from official government reports, performance evaluations, and local regulations related to human resource management. The findings show that the implementation of talent management in Cirebon Regency has been initiated structurally through the issuance of regulatory instruments and the formation of a task force. However, at the operational level, the process has not been fully optimal. The main constraints include limited understanding of talent management among civil servants, absence of standardized performance evaluation systems, and weak inter-departmental coordination in identifying and developing potential talents. In addition, technological support systems such as the digital database and information integration between agencies remain inadequate. The study concludes that successful implementation of talent management requires not only regulatory support but also organizational commitment, leadership, and systematic competence development. The Cirebon Regency Government is advised to strengthen institutional capacity, improve human resource planning, and integrate information systems to support evidence-based and meritocratic personnel management.